Akses Usaha Kecil dan Mikro (UKM) terhadap Kredit Usaha Rakyat (KUR) dan Dampaknya terhadap Perkembangan Usaha: Kasus UKM di Kota Mataram - Embun Suryani; Sri Wahyulina; Siti Aisyah Hidayati (Universitas Mataram, 2019)
Small and Micro Enterprises (SMEs) have a significant role for Indonesia's gross domestic product and employment. However, most SMEs face capital constraints and limited access to formal financial institutions. Kredit Usaha Rakyat (KUR) Fund is one of the credit programs established by the Indonesian Government to overcome capital constraints on SMEs. The study aims to analyze the ability of SMEs to access the KUR loans and the loan’s impact on business development. Primary data was obtained from interviews of 40 respondents who are SMEs in Mataram City. Ability to access the KUR loans was analyzed by logistic regression method while Ordinary Least Square (OLS) was employed to analyze the impact of KUR loans on business development. The result of logit regression shows that the variable of savings and sales influence the ability of SME to access the KUR loan. The KUR funds granted are able to increase SME's sales value by 82.03 percent from 3.47 billion rupiah to 6.31 billion rupiah per year. Based on the OLS analysis, the ability of SMEs to access capital derived from KUR funds has a positive and significant impact on the value of SME business development.